Melindungi Akidah Anak dari Bahaya Dunia Modern Melalui Pendidikan Keluarga - Irwan Sulistyanto; Yuslia Styawati (Indonesian Journal of Humanities and Social Sciences, 2022)
The Muslim personality is formed from an early age, parents as a Muslim must have a quality belief in monotheism. But it would be nice if parents also understand monotheism materials, so that parents can equip their children with knowledge that is supported by the example of monotheism so that the personality of a true Muslim is formed. The family is the first environment for the formation of the unity of the child. In writing this scientific paper, the author uses the type of research "library research" which is a study carried out to solve a problem using library materials. This study found that parents are the main element for the establishment of monotheism in the family, so that everyone is required to have good monotheism, so that they can equip their children with monotheism and materials that support it, besides that children can see their parents as role models who provide knowledge at the same time. experience, and direction. In addition, Nashih Ulwan explained that in forming a child's creed requires supervision, so that the child's condition is always monitored. Universally, Islamic principles teach parents to always supervise and control their children to be safe in this world and the hereafter.